Global Health Organizations in Narcotic and Psychoactive Substance Control - Rana Elttayef Jasim; Adnan Hmeed Hamada (Indonesian Journal of Law and Economics Review, 2025)
Global drug abuse presents a growing public health and security crisis, fueled by complex socio-economic and psychological factors. Specifically, psychoactive substances threaten not only individual well-being but also the stability of communities and national development. While international frameworks exist, the effectiveness of the World Health Organization (WHO) in combating this threat remains underexamined. This study aims to evaluate the WHO’s institutional role, legal authority, and operational strategies in addressing drugs and psychoactive substances at global and regional levels. The findings reveal that WHO plays a critical role through international health policy coordination, technical support, and scientific assessment, especially via collaboration with entities such as the UNODC and INCB. The novelty of this research lies in its integration of legal analysis and health-based strategies, highlighting WHO’s function not only in treatment and prevention but also in legislative guidance and international drug classification. Implications suggest that sustained global cooperation, policy alignment, and WHO-backed health systems strengthening are vital to effectively combat drug proliferation and reduce its societal impact. This study contributes to public health policy discourse by proposing a model of comprehensive, evidence-based international response.Highlight : The WHO plays a central role in coordinating global efforts to combat drugs through health-focused, rights-based strategies. Social, economic, and psychological factors are deeply intertwined in the spread of drug use, making prevention multifaceted. Collaboration between WHO, UNODC, and member states is essential for developing treatment, legislation, and awareness programs. Keywords : World Health Organization, regional organizations, drugs, psychoactive substances, international cooperation